Soil 14CO2 Source Apportionment for Biodegradation in Contaminated Soils in Permafrost Climates: A Novel Technique for Rapid Sample Collection by Barium Carbonate Precipitation - Reynolds, Lindsay (Université d'Ottawa / University of Ottawa, 2019)
The rate of biodegradation of hydrocarbon contaminated soils can be studied using the radiocarbon (14C) content of CO2 efflux from the ground surface over an impacted area.14C is used as a tracer to distinguish modern 14C CO2 from natural respiration processes and 14C depleted CO2 derived from petroleum degradation. Studies have shown that this analysis provides reliable, quantifiable data and an effective means of correcting for background CO2 which may present some natural depletion from older subsurface organics. The study area for this project is a remote community in Northern Yukon where organic rich sediments overlying continuous permafrost are contaminated by diesel oil. An objective of this study was to evaluate the use of 14C to quantify background CO2 in permafrost soils with abundant, older labile organics. A second objective was to test a new sampling technique to facilitate sample shipment from remote sites, which traps soil CO2 in small sealed exetainers as a solid barium carbonate. Data obtained from established radiocarbon sampling procedures and this new novel approach were shown to be comparable and reproducible. This technique facilitated both sample collection and shipment as well as analysis by accelerator mass spectrometry (AMS), allowing for rapid, efficient sampling techniques to be deployed in remote areas. Results of this study show the carbonate method to be an economical and effective sampling method, and used at the Old Crow site, demonstrated that under current climate conditions, older organics in the subsurface do not confound the use of 14CO2 for source zone biodegradation assessment at this hydrocarbon impacted permafrost site.
Keywords: radiocarbon; biodegradation; barium carbonate; permafrost